What are the current financial strategies (2014) that could implement the colombian financial institutions to mitigate the risk of fraud in your financial products? (2014)
This paper is based on research a case where the question What are the strategies that should be present financial institutions and that could be implemented to mitigate the risk of fraud when issuing financial products and generated ? and investigate if these entities are developing a process or method when analyzing applications to detect such fraud investigation in this case will in a first step an approximation of the current state of fraud in financial institutions in Colombia and based in some surveys, studies, research and thesis on the topic determine the impact it has had on the financial sector and the development of economic activity of these companies that are most threatened with the topic. Following this by means of an instrument designed according to the research variables and sources that were used to develop the case, schematically show the different factors that were determined in the document review, statistics and data that will instead the analysis of results and corresponding recommendations to establish mechanisms and strategies for consideration by the entities could reach implemented in their organizations in order to mitigate the risk of fraud and reduce the percentage of operating loss this will brings in his business, now it is also important to reach set some of the demographic, economic and financial characteristics that could generate alerts to financial institutions at the time of analyzing requests for credits.